The effectiveness of curricular methods and means in the constant development of the psychomotor potential of 14-15-year-old handball women players according to their specialization within team - Verejan Galina; Verejan Ruslan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2023)
In this article, there was presented informationregarding the significance of handball women players' specialization in playing positions in their competitive performances at the current stage of handball development. The types of playing positions in handball, their sports-motor characteristic and the need for athletes' specialization at an earlier age were also revealed. Thus, the effectiveness of the game activity of the handball team in general and of each individual player is characterized by the degree to which the individual psychological personality traits of the athlete correspond to the character of the function or position occupied by the handball woman player [6,8,16]. If the personality traits do not correspond to the activity performed, it affects the state of the player and directly influences the quality of the performance of the sports activity [1,8,10,12]. The review of the specialized literature revealed that little research has been done on the specifics of how personality traits affect the outcomes of the actions of handball women players with different specialties. Additionally, it is well established that an athlete's personality, which is shaped by their sport, controls their activism, efficacy, and outcomes.